The determinants of mobile operator switching and policy implications in developing countries: A case study of Thailand - Chutipong Keesookpun; Hitoshi Mitomo (International Telecommunications Society (ITS), 2013)
This paper presents the analyses of the determinants of mobile carrier switching behaviour based on the idea that such the behaviour is the evidence of competition in the mobile market. Indeed, with the possibility to change a mobile service provider, there will be less concentration of customers towards any particular operator, and more distribution of market share among all competitors because the newcomer company can offer its competitive services and gain more subscribers. In order to extract the factors affecting switching decision, both quantitative and qualitative analyses are employed. Binary logit estimation is used as the quantitative method, while qualitative outcomes are derived from the composition of responses regarding carrier switching intention. This study uses a modified estimation model incorporating carrier-related switching costs inspired by Grzybowski (2008). Nevertheless, it is the analysis of a developing country in which Thailand is selected as ground for investigation. The data is collected from surveys randomly distributed within the whole country...
Keywords: 330